IS TURKEY READY TO JOINT THE EUROPEAN FISCAL UNION? - Georg Friedrich SIMET (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Since Turkey was officially recognized as a candidate for full membership in 1999 and negotiations were started in 2005 its membership bid has become and still is a major controversy in the ongoing enlargement process. This controversy contributes not only to the valuation of modern Turkey’s social, cultural, political but also its economic situation. Most statements are based on scenarios derived from the perspective on how Turkey’s membership would influence the EU as a whole and/or some of its member states. The development of Turkey as EU member was rarely researched. In particular it was not studied how Turkey’s membership would change Turkey and how these changes would re-influence the development of the EU in a longer run. The present financial, debt crisis in the EU led to intensified short-term oriented analyses on just financial aspects. In order to define and discuss pros and cons of Turkey’s accession it is not sufficient anymore to focus almost exclusively on the effects of Turkey’s accession to the EU. Turkey is to be analyzed from three further perspectives and scenarios: 1) How will Turkey develop as non-member state? 2) How would Turkey develop as a member-state? And 3) How would Turkey as a member state re-influence the EU? As the present economic crisis of the EU (for instance about 46 % of young people in Spain are jobless) is aggravated by a major financial crisis in the Euro zone, the economic and financial perspectives of development have to be moved into focus. The “Europe 2020 Strategy” points the way, as it provides indicators to measure the EU’s development from a long-termed perspective. Growth “at EU and national levels” has to be “smart”, “sustainable” and “inclusive”. Accordingly, “five targets were identified: (1) 75 % of the population aged 20-64 should be employed, (2) 3% of the EU's GDP should be invested in R&D, (3) The "20/20/20" climate/energy targets should be met, (4) The share of early school leavers should be under 10% and at least 40% of the younger generation should have a tertiary degree or diploma, (5) 20 million less people should be at risk of poverty. In the following paper it will be discussed, if or how Turkey could meet these aims and if the EU could meet them if Turkey would become and be a member state. The EU’s strategy targets will be complemented by financial targets, as the EU recently pushes ahead with a fiscal union. It will be checked if Turkey could become a Euro-country or at least join the fiscal union within the next decade. This will be investigated by looking at the Maastricht Criteria as well as the possibility to implement and meet the restrictions of the debt brake